2021
DOI: 10.3390/su13073711
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Virtual Laboratory for Physics Subjects in Moroccan Universities

Abstract: Laboratory experimentation has a vital role in science education. With the potential offered by information and communication technologies for the educational domain, virtual laboratories have emerged as a valuable alternative to face-to-face, hands-on laboratories. Moreover, the possibility of virtual laboratories opens new perspectives for higher education sustainability. They are a perfect approach for training learners to understand scientific principles in many fields of science by offering them the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 86 publications
2
33
0
11
Order By: Relevance
“…Confirming the results of this analysis, it has been explicitly proven that the reasoning skills of STEM students who are treated with learning using virtual simulations in an LMS (e-learning) platform are better than face-to-face learning using the expository method. The results of this study are in accordance with what was found in previous studies, that virtual simulations can improve students' thinking skills [24]. In another study it was found that computer-based simulation had a positive impact on students' reasoning abilities [33].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Confirming the results of this analysis, it has been explicitly proven that the reasoning skills of STEM students who are treated with learning using virtual simulations in an LMS (e-learning) platform are better than face-to-face learning using the expository method. The results of this study are in accordance with what was found in previous studies, that virtual simulations can improve students' thinking skills [24]. In another study it was found that computer-based simulation had a positive impact on students' reasoning abilities [33].…”
Section: Resultssupporting
confidence: 92%
“…However, we are optimistic about the current massive technological developments that can mediate the teaching of modern physics in more interactive ways and can visualize abstract concepts in physics. Previous studies have recommended the use of virtual simulations in teaching science concepts, and it has resulted in better concept mastery, a better preference for scientific theory, and an increase in students' thinking skills [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moroccan universities developed virtual laboratories and implemented them in the 12 science faculties in Morocco. The study further observed that virtual laboratories support adopting the proposed learning environment in laboratory educational procedures as an alternative to physical laboratories (El Kharki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 76%
“…Sun et al studied the differences in learning performance between learners in different environments by comparing the traditional learning environment with the learning environment combined with virtual reality, and found that the learning performance of learners in the virtual reality environment is better 24 . The University of Morocco has evaluated teachers and learners in a virtual learning environment, and the results show that the use of virtual laboratories has a positive impact on learning outcomes 25 . Badilla et al assessed how teaching and learning processes can be facilitated in a 3D virtual environment 26 .…”
Section: Introductionmentioning
confidence: 99%